Características da higiene bucal associadas à abrasão gengival e ao risco de progressão para recessão gengival - Santi, Samantha Simoni (2022)
Gingival abrasion (GA) is defined as a loss of substance or structure of the gingiva and/or oral mucosa caused by mechanical and/or chemical forces. It is hypothesized that overlapping AGs, caused by daily tooth brushing, can lead to the onset and/or progression of gingival recession (GR). Thus, the present thesis is composed of two articles, whose main outcomes are GA and GR. The first study, with a cross-sectional observational design, aimed to verify associations between oral hygiene characteristics and GA in 688 individuals living in a rural area in southern Brazil. The extent of GA was determined by the number of abrasions per individual. The associations between GA and variables at the site, tooth and individual level were determined using multilevel Poisson regression. Brushing frequency ≥ 2 times a day (RR=2.03; 95% CI: 1.12 – 3.00), brushing with a hard/medium bristle brush (RR=2.32; 95% CI: 1.29 - 3.45), visible dental biofilm (RR=0.87; 95% CI: 0.79 – 0.99) and gingival inflammation (RR=0.80; 95% CI: 0.62 – 0.95) were significantly associated with the extension of GA. The second study was a network meta-analysis (NMA), whose objective was to identify which feature(s)/design of toothbrushes offer the lowest risk of occurrence of AG and GR. The MEDLINE (PubMed), EMBASE, Cochrane (CENTRAL), Scopus Web of Science and Lilacs databases were searched for randomized controlled trials (RCTs) that have compared two or more types of toothbrushes for GA and GR outcomes. In total, six and seven RCTs were eligible for GA and RG, respectively, comparing four types of interventions for each outcome [(manual toothbrushes with 1) rounded bristles, 2) tapered bristles, 3) bristles at different heights) and 4) power toothbrushes]. No significant differences were found between the four groups for both outcomes. Analysis of the surface under the cumulative ranking curve placed hand brushes with rounded filaments and filaments at different heights in first and second place, respectively, for the GR outcome. For GA, power toothbrushe and manual brushes with rounded filaments were in the same positions, respectively. Also, the results of direct meta-analyses showed that soft bristle brushes are protective for GA when compared to medium bristles [0.73 (CI 0.58;0.91)] and that power toothbrushe present less GR progression when compared to manual brushes [-0.11 (CI -0.17; -0.04)]. These results support the hypothesis that, among the different soft toothbrush options, differences in design/characteristics do not seem to exert an important effect on GA and GR, suggesting that other factors (eg brushing technique/force, gingival biotype) play a major role in the development of both outcomes.